Analysis of Urban Built-up Expansion Based on Combination of Spectral Indices in Surabaya City - Ramadhan, Fendra Dwi; Hariyanto, Teguh; Handayani, Hepi Hapsari (Departemen Teknik Geomatika ITS, 2021)
The urban built-up land indicates the physical changes of the city that represent the development indicator in the city of Surabaya. The expansion of urban built-up land needs to be monitored to control and direct urban areas development. In this study, the identification of urban built-up land was conducted by applying a combination of algorithm-based spectral indices consisting of combination A (UI – NDVI – MNDWI) and combination B (NDBI – NDVI – MNDWI) with the spatial expansion analysis that focused on the speed of the urban built-up land expansion and the direction of change of the urban built-up object. Based on the results, the proposed spectral indices combination able to identify the urban built-up land pixels including bare land that free of vegetation and water body object. The pattern of the urban built-up land direction shows a tilt toward the west and east side of the city of Surabaya, while the speed of change shows that combination A and combination B have the same trend, there are a decreasing number of built-up land from 2015 to 2017 and an increasing number of built-up land from 2017 to 2019.